Dampak Alih Fungsi Lahan Pertanian Pangan ke Perumahan Terhadap Ketahanan Pangan Berkelanjutan di Desa Lubuk Empelas Kecamatan Muara Enim Kabupaten Muara Enim - Safety A, Iqro Kurnia (Oryza : Jurnal Agribisnis dan Pertanian Berkelanjutan, 2024)
Agribusiness and Sustainable Agriculture is a journal published by the department of agriculture for The objectives of this study are: (1) To identify the factors that cause the community to change the function of agricultural food land to housing in Lubuk Empelas Village, Muara Enim District, Muara Enim Regency. (2) Identifying the socio-economic and geo- physical impacts of the community after the activity of changing the function of agricultural food land to housing in Lubuk Empelas Village, Muara Enim District, Muara Enim Regency. (3) Analyze the steps that have been taken by the regional government in facing the threat of changing the function of agricultural food land to housing in Lubuk Empelas Village, Muara Enim District, Muara Enim Regency. The research method used is a qualitative method. The sampling method in this study used a simple random sampling method (Simple Random Sampling), which is a random sampling method with a sample size of 44 farmers. Data were collected by taking primary data and secondary data. The results of the study show that (1) The factors that influence the conversion of land to housing in the village are demography, economy, Myopi behavior, the statutory system. Of the 44 respondent farmers, 10 people stated that population density was a factor in the occurrence of land conversion, 13 people stated that economic factors were the reason for land conversion, 10 out of 44 respondent farmers stated that the farmers paid less attention to what would happen in the long term, causing it to occur. 10 other people stated that the farmers still did not know the legal system regarding the transfer of land functions. (2) The land conversion has an impact on education in the village, after the land conversion occurs the community realizes the importance of education so that the level of education increases. The land conversion has increased farmers 'income, but some also admit that farmers' income has decreased. (3) An institutional approach by issuing Perbup No. 14 of 2018 concerning the Plan for the Protection of LP2B Sustainable Food Agricultural Land in Muara Enim Regency and a social approach by providing counseling to farmers regarding land conversion.